Strategi Pemulihan Kepariwisataan Kota Pekalongan pada Masa Adaptasi Kebiasaan Baru - Hartati Hartati; Choliq Sabana; Moh. Projo Angkasa; Sobrotul Imtikhanah; Ahmad Syakir Kurnia (JURNAL LITBANG KOTA PEKALONGAN, 2021)
The presence of COVID-19 as a pandemic, determined by WHO, has destroyed all activities in society, including the people of Pekalongan city.  The Covid-19 virus, which initially had an impact on the health sector, it immediately turned out to also have a domino effect on other sectors, such as the economic, as well as the social one; including the tourism. Restrictions on human movement from one place to another, prohibition of crowding and avoiding crowds make tourist objects deserted by visitors. Considering this pandemic is not known when it will end, and then all parties must prepare themselves with a new custom adaptation order. Of course, it requires the readiness of all parties, both local governments and tourism actors in Pekalongan City. This study is a qualitative descriptive, and data collection is taken by conducting a survey to each object that is examined with a question guide.  The results of the study stated that the compliance of managers, employees and visitors in the modern market and hospitality area was high with a value from 85% to 100%. On the other hand, the compliance of managers, employees and visitors in the traditional market area of batik village, wholesaler, batik museum tourism with a compliance value of the Health protocol was from 50% to 75%. Furthermore, compliance of managers, employees and visitors in the Sari beach tourism area, open space areas, religious tourism and restaurants with a value of compliance with the Health protocol was from 20% to 60%. The majority of non-compliance is due to the absence of punishments for violations of Health protocols.  Keyword:   Covid-19, tourism, new normal